Peran KUA Dalam Mengatasi Permasalahan Wali Nikah di Kecamatan Medan Deli Kota Medan Sumatera Utara - Muhammad Hazazunda; Muhammad Nuh Siregar; Hasbullah Fauzan Rambe (Tarbiatuna: Journal of Islamic Education Studies, 2023)
This internship report raises issues regarding guardians in marriages that occurred in the Medan Deli sub-district, Medan city, North Sumatra. During our internship we also conducted research and found that there were still many people who did not know the lineage of their marriage guardians, this was the background for researchers to research more about guardianship that occurred in Medan Deli District, Medan City, North Sumatra. This study aims to find out the description and factors that cause people not to know their marriage guardian lineage in Medan Deli District, Medan City, North Sumatra. This research is a field research located at the Office of Religious Affairs (KUA) in Medan Deli District, Medan City, North Sumatra. To collect the necessary data the author uses interview techniques, direct observation, and searches for several literature studies. The results of the study show that many people still do not know their marriage lineage. Especially for people who don't have parents, an only child, and their guardian siblings who have died and their whereabouts cannot be found. Then the solution is that the head of the Office of Religious Affairs (KUA) can become the judge's guardian and that is legal. Suggestions from this study are that the people of Medan Deli District, Medan City, North Sumatra know more about the lineage of their marriage guardians so that they know more about how to find out their marriage lineage properly and correctly. the marriage guardian because the lineage of the marriage guardian is important if the lineage of the marriage guardian is wrong then the marriage is invalid. Keywords: Role, Marriage guardian, Marriage,